Nuclear access and action of Notch in vivo. - Struhl, G.; Adachi, A. (Cell, 1998)
The Drosophila Notch (N) gene encodes a conserved single-pass transmembrane receptor that transduces extracellular signals controlling cell fate. Here, we present evidence that the intracellular domain of Notch gains access to the nucleus in response to ligand, possibly through a mechanism involving proteolytic cleavage and release from the remainder of the protein. In addition, our results suggest that signal transduction by Notch depends on the ability of the intracellular domain, particularly the portion containing the CDC10 repeats, to reach the nucleus and to participate in the transcriptional activation of downstream target genes.